Efektivitas Bimbingan Kelompok Pendekatan Muhasabah dalam Meningkatkan Sikap Religius Siswa - Ardimen, Ardimen; Zahira, Nadia; Silvianetri, Silvianetri; Hidayat, Rahmat (Universitas Islam Negeri Madura, 2023)
A person's happiness is not only influenced by material completeness, but is also very much determined by religious attitudes. While the real conditions in the field found students to have a low religious attitude. For this reason, the religious attitude of students needs to be improved. One of the efforts to improve religious attitudes is through group guidance with a muhasabah approach. The purpose of this study was to analyze the effectiveness of the muhasabah approach group guidance in improving students' religious attitudes. This type of research uses a quantitative experimental method with a one group pee-test-post-test design. Determination of the sample using simple random sampling with a sample of 56 students. The data collection technique used is a non-test technique using a liker scale, namely the scale of religious attitudes. The results showed that group counseling with the muhasabah approach was effective in increasing students' religious attitudes as seen from the dimensions of belief, the dimensions of religious practice, the dimensions of appreciation, and the dimensions of the consequences of practice.